Mg-vacancy-induced Ni-vacancy clusters: highly efficient hydrogen production from cellulose. Issue 29 (16th July 2020) - Zhang, Jian; Zhu, Yanru; An, Zhe; Shu, Xin; Ma, Xiaodan; Song, Hongyan; Wang, Wenlong; Zhao, Jieqiong; Cao, Xingzhong; He, Jing
Abstract : An H2 yield of up to 70.4% has been achieved from APR of cellulose due to defect-boosted C–H/C–C bond cleavage. Abstract : H2 production from aqueous phase reforming (APR) is of great importance, but an enhancement in the H2 production efficiency is required. Our previous work reported the catalytic production of H2 over metal oxide (MMO)-supported Ni derived from Ni-containing layered double hydroxides (Ni-MgAl-LDHs). Herein, we report the catalytic production of H2 from APR of cellulose over MMO-supported defect-rich Ni derived from Ni-MgAl-LDHs with abundant Mg(ii ) vacancies (VMg ). The well-retained VMg during calcination under an H2 atmosphere induced the formation of Ni vacancies not only at the Ni–MMO interface, but also on the surface of the Ni particles. An H2 yield of up to 70.4% was achieved via the APR of cellulose over the defect-rich Ni–MMO, which is almost 2.5 times that from the APR of cellulose reported to date (∼30%). A combined investigation via quasi in situ XPS, EPR, PAS, and in situ FT-IR verified that the Mg vacancies on the support surface facilitate the cleavage of the C–H bond, while the Ni vacancies on the Ni particles boost the breakage of the C–C bond.